2019 ESC Guidelines for the diagnosis and management of acute pulmonary embolism developed in collaboration with the European Respiratory Society (ERS): The Task Force for the diagnosis and management of acute pulmonary embolism of the European Society of Cardiology (ESC). Issue 3 (19th September 2019) - ; Konstantinides, Stavros V.; Meyer, Guy; Becattini, Cecilia; Bueno, Héctor; Geersing, Geert-Jan; Harjola, Veli-Pekka; Huisman, Menno V.; Humbert, Marc; Jennings, Catriona Sian; Jiménez, David; Kucher, Nils; et al.
New @ESCardio Guidelines for the Diagnosis and Management of Acute #PulmonaryEmbolism developed in collaboration with @EuroRespSoc now available: #cardiotwitter @erspublications http://bit.ly/2HnrJaj